Examining proximity factors in public-private collaboration models for sustainable agri-food system transformation: a comparative study of two rural communities - Katrin Martens; Katrin Martens; Sebastian Rogga; Ulrike Hardner; Annette Piorr (Frontiers in Sustainable Food Systems, 2023)
Collaboration among local actors is considered an important precondition for a sustainable transformation of the regional agri-food system. To date, however, little is known about the social innovation capacity of local farmers when it comes to the establishment of alternative food networks. This is especially true for farmers’ collaborations with local government officials, which are becoming increasingly important in establishing sustainability-oriented markets for local products and services, especially in the agricultural sector that is often rooted in rigid logics, supply chains and institutions. Therefore, this paper aims to explore the concept of proximity as an analytical lens to understand private-public collaboration models that aim at facilitating sustainable transformation in rural areas. Drawing on concepts from innovation geography, this paper considers the influence of geographic, cognitive, institutional, organizational and social determinants of collaboration, enabling an evaluation of the social innovation capacity of local private and public actors. This theoretical approach helps to disassemble and differentiate social innovation processes to determine success strategies. The paper studies two rural communities where mayors aim to establish local food stores with regional products and, therefore, seek collaboration with local farmers. While the empirical aspect of the study is limited, the two cases provide an opportunity to test the theoretical framework. The proximity approach can be significant for regional agri-food system transformation and steering social innovation processes by considering the distinct capacities of actors. Our conclusion is that the examination of the absence and degree of proximity facilitates a better understanding of practical recommendations to promote agri-food system transformation.